An adaptive control procedure for a fuzzy quality characteristic. (16th August 2010) - M'Hallah, Rym; Melloy, Brian J.
A new adaptive economic control scheme for a fuzzy quality characteristic is introduced in this paper. The control scheme includes a sampling interval, a sample size, and an action that are all variable. It minimises the total cost of a multistage process over a short production run. The state of the process is described via a membership function and the aggregate fuzzy membership function of the sample is used instead of commonly used measures of centrality. This scheme, originally designed for an actual industrial case, can be applied to a variety of manufacturing processes where the quality characteristic of interest is fuzzy or where the sampling outcome is expressed via linguistic variables. Extensive computational results show that it brings about sizeable savings. In particular, it is less costly than schemes where the static control limits are based on the fuzzy mean deviation and two-way classification economic adaptive control schemes.